2017
DOI: 10.1111/jphd.12210
|View full text |Cite
|
Sign up to set email alerts
|

Primary dental care evaluation in Brazil: an item response theory approach

Abstract: Although the analyzed items are insufficient to determine the performance of OHTs, the items related to prosthesis and oral cancer tend to discriminate high-performing OHTs from other OHTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 27 publications
0
23
0
2
Order By: Relevance
“…According to the results of evaluation of the health teams, they can receive a financial incentive for the continuity of systematic progress. Previous studies based on data from the PMAQ-AB have already evaluated the performance of dental procedures [8, 9] and oral health preventive procedures [10], as well as the interrelation between PHC and specialized care [11]. However, despite financial incentives provided by the Brazilian MS to expand and qualify PHC, no detailed evaluation of the performance of prosthetic procedures has been carried out as yet.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of evaluation of the health teams, they can receive a financial incentive for the continuity of systematic progress. Previous studies based on data from the PMAQ-AB have already evaluated the performance of dental procedures [8, 9] and oral health preventive procedures [10], as well as the interrelation between PHC and specialized care [11]. However, despite financial incentives provided by the Brazilian MS to expand and qualify PHC, no detailed evaluation of the performance of prosthetic procedures has been carried out as yet.…”
Section: Introductionmentioning
confidence: 99%
“…The study results are in agreement with previous studies which also showed that these regions have better indicators. 27,28,29 Differences in the quantities of opioid analgesics dispensed may reflect the existence of differences in access to these drugs between states. Most Brazilian states have relatively low dispensing rates of opioid analgesics for dental care purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The result was graphically illustrated as biplot [11]. Under the Item Response Theory (IRT) approach three-parameter logistic model were applied [12][13][14][15]. Item difficulties, item discriminations, guessing and item information were calculated.…”
Section: Discussionmentioning
confidence: 99%